Anatomy Education Environment Measurement Inventory (AEEMI): a cross-validation study in Malaysian medical schools - Siti Nurma Hanim, Hadie; Muhamad Saiful Bahri, Yusoff; Wan Nor, Arifin; Fazlina, Kasim; Zul Izhar, Mohd Ismail; Mohd Anizam, Asari; Husnaida, Abdul Manan @ Sulong; Asma’, Hassan; Tg Fatimah Murniwati, Tg Muda; Yasrul Izad, Abu Bakar; Rasheeda, Mohd Zamin; Elvy Suhana, Mohd Ramli; et al. (BMC Medical Education, 2021)
Background The Anatomy Education Environment Measurement Inventory (AEEMI) evaluates the perception of medical students of educational climates with regard to teaching and learning anatomy. The study aimed to cross-validate the AEEMI, which was previously studied in a public medical school, and proposed a valid universal model of AEEMI across public and private medical schools in Malaysia.